2015
DOI: 10.1210/jc.2015-2232
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Spectrum of Ehlers Danlos Syndrome in Patients With Congenital Adrenal Hyperplasia

Abstract: CAH-X syndrome is commonly found in CAH due to 21-hydroxylase deficiency and may result from various etiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(126 citation statements)
references
References 38 publications
4
119
1
2
Order By: Relevance
“…A formal clinical evaluation was not performed in the first degree relatives of patients in this study, but the family history revealed that in 8 of 33 (24%) carrier individuals joint hypermobility was present (36% of the mothers, 9% of the fathers, 27% of the tested siblings), which is probably to be slightly higher than in the general population. Furthermore, patients with congenital adrenal hyperplasia and a contiguous deletion of CYP21A2 and TNXB resulting in TNX haploinsufficiency are reported to have a more severe phenotype (14,15). This was similar as the findings in the 10 haploinsufficient TNXB subjects investigated in this study on neuromuscular features: asymptomatic hypermobility (Beighton score ≥ 5) was detected in four female patients [Beighton scores not published; patients included in study by Voermans et al (7)].…”
Section: Clinical Featuressupporting
confidence: 88%
See 2 more Smart Citations
“…A formal clinical evaluation was not performed in the first degree relatives of patients in this study, but the family history revealed that in 8 of 33 (24%) carrier individuals joint hypermobility was present (36% of the mothers, 9% of the fathers, 27% of the tested siblings), which is probably to be slightly higher than in the general population. Furthermore, patients with congenital adrenal hyperplasia and a contiguous deletion of CYP21A2 and TNXB resulting in TNX haploinsufficiency are reported to have a more severe phenotype (14,15). This was similar as the findings in the 10 haploinsufficient TNXB subjects investigated in this study on neuromuscular features: asymptomatic hypermobility (Beighton score ≥ 5) was detected in four female patients [Beighton scores not published; patients included in study by Voermans et al (7)].…”
Section: Clinical Featuressupporting
confidence: 88%
“…Cysteine at position 4058 is predicted to be engaged in a disulfide bond with Cys4028, which stabilizes the structure of the C-terminal fibrinogen domain of TNX (15). It concerns here a 120 bp deletion, c.11435_11524 + 30del, which abolishes part of exon 35 en intron 35 of TNXB.…”
Section: Molecular Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…This 8.5kb CYP779f/Tena32F amplicon is able to reveal TNXA/TNXB chimeras and has been utilized to study CAH-X patients. 41,43,44 Hannah-Shmouni et al Page 7…”
Section: Molecular Analysis Of Cyp21a2 Mutationsmentioning
confidence: 99%
“…Additional chimeric genes have subsequently been identified and overall 9% of patients with CAH due to 21-OHD are estimated to have CAH-X, a connective tissue dysplasia, in addition to having CAH. 43 The deletions associated with CAH-X are TNXA/TNXB chimeras ( Figure 4) and 3 types of chimeric genes have been identified to date, designated CAH-X CH-1, CAH-X CH-2, and CAH-X CH-3. 41,43,44 CAH-X CH-1 involves the 120bp deletion in the exon 35 region of TNXB and leads to haploinsufficiency with reduced tenascin-X; CAH-X CH-2 involves the c.12174C>G (p.Cys4058Trp) variant in exon 40 of TNXB, which does not alter tenascin-X expression but rather causes a dominant-negative effect due to the loss of a critical disulfide bond in the tenascin-X fibrinogen-like domain; and CAH-X CH-3 involves a cluster of three variants and also causes a dominant-negative effect.…”
Section: Cah-x Syndromementioning
confidence: 99%